Nanorods and Nanocomposites 2020
DOI: 10.5772/intechopen.88712
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Nanostructures for Li-Ion Batteries

Abstract: Due to the energy crisis, the focus on the study of new materials has increased vastly. For the increasing demand of renewable energy, there are different ways suggested to attain that, which include the rechargeable batteries and the need to achieve them at smaller costs and for longtime use. Lithium ion batteries have gained a lot of attention for that specific reason. Along with the experiments, the easier way to understand and increase the efficiency of these materials for LIBs is to study them through sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…From the theoretical investigations, it was seen that the SW defects in 2D materials significantly alter the electronic properties such as fast charge transfer and display most active sites for metal-ions adsorptions. [136,[142][143][144][145] Recently it was reported that the SW defect significantly enhanced the electrochemical performance of Li-ion battery. [136] Figure 3 a (I-IV) shows the BC 3 monolayer with pristine and SW defected sheet.…”
Section: Sà W Defects For Mibsmentioning
confidence: 99%
“…From the theoretical investigations, it was seen that the SW defects in 2D materials significantly alter the electronic properties such as fast charge transfer and display most active sites for metal-ions adsorptions. [136,[142][143][144][145] Recently it was reported that the SW defect significantly enhanced the electrochemical performance of Li-ion battery. [136] Figure 3 a (I-IV) shows the BC 3 monolayer with pristine and SW defected sheet.…”
Section: Sà W Defects For Mibsmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) are considered a new energy storage device. They have dominated the portable electronic market since their first commercialization by Sony in 1991, 6,7 mainly due to their higher energy density, long life, low toxicity, fast charging, and environmental friendliness. Nevertheless, the high cost of lithium and its low availability limit the future application of these batteries in commercial storage devices.…”
Section: Introductionmentioning
confidence: 99%